El léxico neoplatónico en la poesía francesa del Renacimiento - García Peinado, Miguel Ángel (Anales de Filología Francesa, 2010)
In this article I approach firstly the different ideas the two most outstanding members of the Pléiade, namely Ronsard and Du Bellay, have on poetry, and secondly, I look into the language of some of the most relevant French Renaissance poets of the second half of the 16th century, who exploit the Neoplatonic topics while drawing on the Florentine Marsilio Ficino’s commentaries on the edition of Plotinus’s work. Finally, it is my purpose here to go into two representative examples of this type of language, some chosen poems by Antoine Héroët, Maurice Scève, Louise Labé and Du Bellay.